Business confidentiality and freedom of expression The evolving jurisprudence of the Strasbourg court - Papp János Tamás (ERA FORUM, 2025)
This article examines the European Court of Human Rights’ evolving jurisprudence on balancing business confidentiality and freedom of expression under Article 10 of the European Convention on Human Rights. It analyses key judgments from Heinisch v. Germany to Boronyák v. Hungary , including Bucur , Matúz , Gawlik , Aghajanyan , and Halet . It explores the six-part whistleblower test formulated in Guja v. Moldova , and explores challenges posed by loyalty duties, chilling effects, and digital-age risks, situating Strasbourg’s approach within broader European whistleblower protection frameworks.